Behind the lens an exploratory study on the level of training of photojournalists from leading national broadsheets (Philippine Daily Inquirer, Philippine Star and Manila Bulletin) and wire agencies (Agence France-Presse, European Pressphoto Agency and Reuters) - Dalupang, Joshua Mark; Espenilla, Renee Louise Pongan; Rara, Ma. Christina Imperial (2012)
"This thesis examines whether photojournalists from Philippine Daily Inquirer, Philippine Star, Manila Bulletin, Agence France-Presse, European Pressphoto Agency and Reuters receive and undergo job-related training. This explores the views and outlooks of chief photographers and photojournalists with regards to training and how it has helped them in news coverage and ethics. As a guide, the researchers used Adam's Motivational theory to find out what motivates the photojournalists and chief photographers to improve. Leontief's Input-output model was also used, which states that training as an input helps in creating a better result. To validate the theories used for this study, the researchers administered surveys and conducted focused interviews with the chief photographers and photojournalists from the news organizations mentioned above. This research determined that competition and training further the performance of photojournalists."
Vita.
Undergraduate thesis (A.B. Journalism)--University of the Philippines.
Keywords: Photojournalists -- Training of -- Philippines